Artificial Intelligence’s Understanding of Religion: Investigating the Moralistic Approaches Presented by Generative Artificial Intelligence Tools - Tsuria, Ruth (Religions, 2024)
As AI becomes more commonplace, it is imperative to investigate the ways in which this technology represents various socio-political concepts and identities, such as religion. To do so, we present several conversations with various AI tools on three religious traditions: Judaism, Islam, and Christianity. From our analysis of these conversations, we noted three important elements: AI struggles to represent complex religious issues; It emphasized diversity of opinions; And it encourages the reader to engage with respect and sensitivity regrading religious issues. We therefore suggest that AI takes an axiologically focused approach towards religious representations.